105 Cardiac Mri Assessment Of Pulse Wave Velocity And Aortic Distensibility Following Treatment Of Aortic Stenosis. (31st May 2014) - Musa, Tarique; Greenwood, John; Uddin, Akhlaque; Fairbairn, Timothy; Kidambi, Ananth; McCann, Gerry; Plein, Sven; Motwani, Manish; Ripley, David; Sourbron, Steven
Abstract : Background: Arterial stiffness is an independent predictor of cardiovascular mortality and can be characterised by CMR measurement of aortic distensibility (AD) and pulse wave velocity (PWV). Aim: To compare AD and PWV in patients with severe symptomatic aortic stenosis before and after receiving TAVI or SAVR. Methods: All patients underwent an identical 1.5T CMR protocol (Intera, Philips or Avanto, Siemens). For AD, blood pressures were recorded immediately prior to multi-phase steady state free precession (SSFP) cine imaging (50 phases) acquired in a plane transverse to the ascending thoracic aorta at the level of the pulmonary artery bifurcation. Aortic contours were drawn offline (QMass V7.5, Medis, The Netherlands) by manual planimetry of the endovascular–blood pool interface at the times of minimal and maximal distension. For PWV, through-plane phase contrast velocity mapping was performed perpendicular to the ascending and descending thoracic aorta at the level of the pulmonary artery bifurcation (breath-hold, single slice, 10 mm thick, 40 phases, typical FOV 350, RFOV 85). Offline analysis was performed using validated in-house software (PMI 0.4) based on IDL 6.4 (ITT Visual Information Systems, Boulder, CO, USA). The velocity encoded images of the ascending and descending thoracic aorta were manually contoured to derive velocity-time curves. The distance (mm) between the two locations was measured manually from in-plane saggital/oblique images of the aortc arch. PWV (m/s) was calculated using the transit-time method. Results: 27 SAVR patients (age 71.8 ± 7.0 years, 75% male, mean EuroSCORE II 1.43 ± 0.44%) and 21 TAVI patients (age 81.7 ± 6.3 years, 52% male, EuroSCORE II 6.32 ± 5.99%) were studied before and 6 months after intervention. SAVR was associated with a significant decrease in aortic distensibility (2.00 ± 1.57 vs. 1.39 ± 0.69 × 10–3 mmHg-1, p < 0.05) whereas there was no change observed in the TAVI group (1.68 ± 0.80 vs. 1.76 ± 0.85 × 10–3 mmHg-1, p = 0.74). SAVR was associated with a significant increase in PWV at 6 months (mean 6.69 ± 5.12 vs 12.13 ± 6.22 ms-1, p = 0.01) whereas there was no change observed in the TAVI group (9.91 ± 9.32 vs. 12.42 ± 9.24 ms-1, p = 0.23). Conclusions: In patients with severe aortic stenosis, SAVR but not TAVI is associated with a significant increase in pulse wave velocity and decrease in aortic distensibility at 6 months suggesting a possible adverse affect on aortic wall elasticity.